Penyuluhan tentang Kenali dan Waspada Corona Virus Diseases of 2019 (Covid-19) pada Acara Hari Bebas Kendaraan Bermotor Kota Padang - Russilawati Russilawati; Irvan Medison; Afriani Afriani; Yessy Susanty Sabri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
Mysterious atypical pneumonia appeared abruptly in Wuhan, China in December 2019. China authority and Word Health Organization (WHO) found out the etiology on January 2020. New strain of Corona virus that eventually called by SARS-CoV2 has been responsible for the Corona virus disease of 2019 (Covid-19). The disease has ability to spread from human to human. These diseases had been pandemic since March 2020. As the start of early spreading we need to give right information about Covid-19 to the community so that the mass panicked could be avoided. We also need to educate community to take right precaution and prevention. These activities aims to spread the right information about Covid-19 and give simple training to performed prevention act so that community can slowdown the disease transmission. Methods: the campaign and health education about covid-19 and training of cough etiquette, right steps of hand washing using water and soap or alcohol based hand rub, and also how to use face mask properly. There were 66 participants that involved in this event. Participants had actively asked information about frequency of hand washing we need to prevent transmission and travel safety. We also performed flash mob so the participants could train cough etiquette, hand washing, and using face mask in fun ways. We ended the activities with competition of hand washing and using face mask properly. The door prize for the winner was hand sanitizer and face mask that they could use as tools to prevent transmission of Covid-19.